(355) Refugees in Egypt: Impacts and Policy Recommendations اللاجئون في مصر: التأثيرات والتوصيات السياسية - Nagla Harb; Fadia Mohammed Abdel Salam; Mahmoud Abd El-Hia; Nihal Abdel Atti Ghwas; Mayar Yehia (Institute of National Planning, 2024)
The global refugee and forced displacement crisis has emerged as a significant and urgent challenge for global development. According to the 1951 United Nations Refugee Convention, a refugee is someone who has fled their country due to fear of persecution based on race, religion, nationality, membership of a social group, or political opinion. The broader category of forcibly displaced people includes those who are forced to move due to persecution, conflict, violence, or human rights violations. Recent data from the United Nations High Commissioner for Refugees (UNHCR) indicates that an estimated 117,3 million people were forcibly displaced worldwide by the end of 2023, with this number projected to reach 130.8 million by the end of 2024. This total includes 32.6 million registered refugees and 7 million asylum seekers. The majority of refugees are hosted by developing countries, where they often place a strain on public services such as housing, healthcare, and education, potentially leading to resource shortages and social tensions. Egypt, a lower-middle-income country, exemplifies these challenges. The number of registered refugees and asylum-seekers in Egypt surged from approximately 109,000 in 2010 to 646,291 according to the UNHCR latest data in May 2024. Government estimates, however, indicate that the total number of displaced people in Egypt could be significantly higher, potentially reaching several million. Unlike many other countries that house refugees in camps, Egypt adopts a different approach by allowing them to live alongside local communities in urban areas. Refugees, particularly Syrians and Sudanese, have access to public services including healthcare and education comparable to that of Egyptian citizens. While Egypt lacks a formal integration policy, it encourages refugees to participate in the workforce, contributing positively to the economy. The surge in the refugee population has sparked concerns and public calls for policy revisions, including proposals for repatriation and restrictions on settlement or naturalization. Recent events, such as the conflict in Sudan, have exacerbated the pressure on Egypt's refugee hosting capacity. In July 2023, the Prime Minister addressed the strain on Egypt's public services during a speech in Rome and appealed for international support. This mounting pressure has prompted the Egyptian government to reassess its refugee hosting policies. This study aims to comprehensively explore the economic, social, cultural, and environmental impacts of hosting refugees in Egypt. By considering both the benefits and challenges. The study further proposes policy recommendations to mitigate negative impacts and foster sustainable refugee integration. A mixed-methods approach is employed. In addition to secondary data, Primary data is collected through an online survey of Egyptian citizens and semi-structured interviews with key stakeholders. Vector Autoregression (VAR) model is employed to analyze the dynamic relationship between refugee influx and key macroeconomic indicators: growth rate, inflation, and unemployment. The Study is divided into four chapters, chapter one establishes a baseline on the current situation of refugees, chapter two analyzes economic impacts, chapter three explores citizen perceptions of social, cultural, and environmental impacts, chapter four highlights successful integration practices in other countries. The findings reveal both challenges and benefits associated with hosting refugees. Economic challenges include increased prices, mainly housing costs, and competition in the low-skilled labor market. However, refugees can also contribute to job creation. The VAR model reveals a dynamic relationship between refugee influx and macroeconomic variables. The impact of refugee influx on inflation (housing and utilities) exhibits a lagged effect. Initially insignificant, then it becomes positive and significant in the later lags, suggesting that refugee settlement leads to increased demand over time. A short-term decrease in unemployment is observed, followed by a potential increase. This suggests a possible substitution effect, as refugee labor participation intensifies competition in the job market as their integration into the economy progresses. Social and cultural negative impacts, as perceived by the surveyed sample, include pressure on health services. However, benefits include the potential for increased social networks. Environmental challenges encompass strain on resources such as water and energy, as well as the potential spread of diseases. Nevertheless, there is the possibility of attracting aid for environmental protection projects.